Underwater data collection using an autonomous float-back sub - Sabbir, Adnan; Ahmed, Sakib (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.